Association between baseline IL‐6 and 1‐year recovery in lumbar radicular pain. (2nd April 2014) - Schistad, E.I.; Espeland, A.; Pedersen, L.M.; Sandvik, L.; Gjerstad, J.; Røe, C.
Abstract Background In the present study, the influence of cytokines on 1‐year recovery in lumbar radicular pain was examined. Methods In total, 110 patients with symptomatic lumbar disc herniation were followed for 1 year. Uni‐ and multivariate linear regression was used to assess the influence of interleukin (IL)‐6, IL‐8, disc degeneration and endplate changes (Modic changes) on the changes in the Oswestry Disability Index (ODI change; primary outcome) and visual analogue scale (VAS) for low back pain (LBP) and leg pain (secondary outcomes). Results Less favourable ODI outcome correlated with higher serum IL‐6 levels (B = −3.41, 95% CI −5.52 to −1.30, p = 0.002), non‐surgical treatment (B = −7.03, 95% CI 1.21 to 12.84, p = 0.018), higher baseline back pain intensity (B = −2.28, 95% CI −3.21 to −1.35, p < 0.001) and low educational level (B = −5.57, 95% CI 0.66 to 10.47, p = 0.027). High VAS for LBP and leg pain at 1 year was associated with high levels of serum IL‐6, higher back pain intensity and longer duration of lumbar radicular pain at baseline. Conclusions High serum IL‐6 levels, but not disc degeneration or Modic changes, were associated with less favourable recovery in patients with lumbar radicular pain. Intense initial back pain, non‐surgical treatment, lower educational level and longer duration of radicular pain before treatment also correlated with a slower recovery the first year after disc herniation.